Kristen etik i et pluralistisk samfund - Nikolajsen, Jeppe Bach (Dansk Teologisk Tidsskrift, 2016)
In recent decades, a growing number of theologians have discussed the challenges and opportunities facing the Christian church as Western societies have become increasingly pluralistic. In a number of articles and books, various issues relating to this situation have been discussed. In continuation of this conversation, the article demonstrates that a tradition for a strong emphasis on the universality of theological ethics has existed in the Danish theological tradition, which is exemplified by reference to Martin Luther, Nikolai Frederik Severin Grundtvig and Knud Ejler Løgstrup. Then, the article presents some empirical and theological arguments for the necessity of a stronger articulation of the particularity of theological ethics. Finally, the article shows how a theological position which expresses the particularity of theological ethics, while at the same time maintaining its universal basis, can contribute with some instructive and constructive perspectives on theological ethical reflections in a pluralistic society.